Comparative Analysis of Carrier based techniques for Single phase Diode Clamped MLI and Hybrid inverter with reduced components - Nunsavath Susheela (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
The multilevel inverters have highly desirable characteristics in high power high voltage applications. The multilevel inverter was started first with diode clamped multilevel inverter. Later, various configurations have been came into existence for many applications. However the multilevel inverters have some demerits such as requiring higher number of components, PWM control method is complex and capacitor voltage balancing problem. The hybrid multilevel inverter presented in this paper has superior characteristics over conventional multilevel inverters. The hybrid multilevel inverter employs fewer components and less carrier signals when compared to conventional multilevel inverters. It consists of level generation and polarity generation stages which involves high frequency and low frequency switches. The complexity and overall cost for higher output voltage levels are greatly reduced. Implementation of single phase 7-level, 9-level and 11-level diode clamped multilevel inverter and hybrid multilevel inverter has been performed using sinusoidal pulse width modulation (SPWM) strategies i.e., phase disposition (PD), alternate phase opposition disposition (APOD). Also these techniques are compared in terms of total harmonic distortion (THD) for various modulation indices and observed to be greatly improved in case of hybrid inverter when compared to diode clamped inverter. The comparative study of performance for single phase diode clamped multilevel inverter and hybrid inverter is analyzed with different loads.  Simulation is performed using MATLAB/ SIMULINK.